Microbiological analysis and detection of anti-bacterial activity of Centella asiatica and Aloe vera samples collected from different areas of Dhaka city, Bangladesh (Stamford Journal of Microbiology, 2017)
The present study was performed to detect the presence of contaminating microorganisms in two commonly available herbal samples (Centella asiatica and Aloe vera) collected from different areas of Dhaka city, Bangladesh and to assess their antibacterial activity. Out of twenty samples (having ten samples of each categories) studied; the range of total viable bacterial count was approximately 103 to 108 cfu/g. Presence of Staphylococcus aureus was found in all the samples, followed by Klebsiella spp. in 15 samples, Pseudomonas spp. in 14 samples, Bacillus spp. in 12 samples, Escherichia coli in 9 samples and Vibrio spp. in 7 samples. Salmonella spp. was detected in neither of the sample. 17 samples showed a high fungal load up to 107 cfu/g. Antibacterial activity of C. asiatica samples was demonstrated against eight laboratory isolates. Only four C. asiatica samples showed activity against Klebsiella spp. On the contrary, Aloe vera samples (12-14) showed antibacterial activity only against Staphylococcus spp.Stamford Journal of Microbiology, Vol.6(1) 2016: 39-43